2011
DOI: 10.1080/01932691003659668
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Oil Deposition Through a Flow Loop

Abstract: In this article, the effect of temperature, pressure, and flow rate on deposition rate has been investigated by using chemical analysis method for calculating the deposit thickness and comparing to heat transfer and pressure drop methods. To do so, an experimental high pressure flow loop setup was designed and constructed to conduct various experiments. Caliper readings at the end of each test showed the chemical analysis method in comparison to the heat transfer and pressure drop methods is superior for depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…[5,12] Pressure is not considered as an important factor for wax deposition, especially for dead or stock tank oils. [2,13] A thorough experimental research on the effect of operating condition in deposition thickness from single phase flow has been reported by Lashkarbolooki et al [2] and Seyfaee et al [3] The patent literature describes many products developed to remove or prevent paraffin deposits, but in spite of these contributions the problem of paraffin deposition was not solved. Good descriptions of chemical inhibitors are given in the literature.…”
Section: Please Scroll Down For Articlementioning
confidence: 96%
See 3 more Smart Citations
“…[5,12] Pressure is not considered as an important factor for wax deposition, especially for dead or stock tank oils. [2,13] A thorough experimental research on the effect of operating condition in deposition thickness from single phase flow has been reported by Lashkarbolooki et al [2] and Seyfaee et al [3] The patent literature describes many products developed to remove or prevent paraffin deposits, but in spite of these contributions the problem of paraffin deposition was not solved. Good descriptions of chemical inhibitors are given in the literature.…”
Section: Please Scroll Down For Articlementioning
confidence: 96%
“…[1,11] Several factors are responsible for the wax deposition in the pipelines, including crude oil composition, temperature, flow rate, thermal history, and pressure. [1][2][3][4] Moreover, the amount of deposited wax is affected by the concentration of paraffins, light ends, and nucleating or inhibiting materials in the crude oil. [5,12] Pressure is not considered as an important factor for wax deposition, especially for dead or stock tank oils.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
See 2 more Smart Citations
“…[1,[10][11][12][13] The previous experimental investigations have shown that crude oils with wax content of at least 2% could cause wax deposition problems. [14][15][16][17] Seyfaee et al [18] experimentally investigated the effect of temperature, pressure, and flow rate on the deposition. They were used chemical analysis method for calculating the deposit thickness.…”
Section: Asphaltenes and Resinsmentioning
confidence: 99%